A lei de acesso às informações públicas em consonância com o patrimônio documental dos municípios da Grande Santa Rosa: recomendações e diretrizes para uma política pública arquivística - Luz, Marco Antônio da (2014)
Critical to the proper functioning of any municipality, the archival documents addition to registering the actions of rulers, regarding the policies and programs of improvements to the municipality, play a key role in the recovery of memory and history of a community. Thus, this study sought to identify the archival situation in regard to the creation and implementation of archives public policies in the municipalities belonging to the Association of Municipalities of Grande Santa Rosa - AMGSR. Initially we sought foundation for designing an conceptual framework essential for the formation of public policy aspects of archive. We also investigated the archival panorama of the region under analysis in order to verify that the difficulties encountered by municipal managers to provide Document Management and Archival Preservation of Documentary Patrimony. Another important aspect of the study, and worth mentioning, is on account of the analysis of compliance with the Law on Access to Public Information and its consequences against Archivology. Note also that because it is a College Graduate Program, is required to submit a product , culminating in the development of some recommendations and guidelines designed to implement Archives Public Policy focused in the Law on Access to Public Information and Archival Preservation of Documentary Patrimony. To achieve the objectives proposed by the study methodology was made a exploratory- descriptive research. It was understood that this would be the best way to study the problem involving archives, documents and municipalities. The operationalization of the research took place from the structuring and implementation of two questionnaires, one Survey with open and closed questions and the other only with open questions, which made possible to collect information and data rich in detail. From the data analysis, it is observed that the archival overview of the study area falls short of emanated by the Constitution of 1988 and by other laws and regulations. The difficulties of municipalities in providing document management and consequently the preservation of the Documentary Patrimony, are due to shy managers' engagement in these tasks, in almost total lack of investments in the archives, the low rate of duly constituted Municipal Archives, the low level of document management tools, and lack of qualified personnel to tasks related to document management. Thus, it is expected that this work is a seed planted, at least in the municipalities that effectively collaborated with the research. It is also expected that the archival panorama of AMGSR region gradually become more favorable, where in the near future can be seen the contributions of study, both with regard to the development of cities, as in matters of cultural patrimony preservation.